Long‐term viability of the northern anthracnose pathogen, Kabatiella caulivora, facilitates its transportation and spread. (5th April 2017) - Barua, P.; You, M. P.; Bayliss, K. L.; Lanoiselet, V.; Barbetti, M. J.
Abstract : The conidia and resting hyphae of the northern anthracnose pathogen of Trifolium species, Kabatiella caulivora, were effectively carried by, and maintained long‐term viability on, a range of materials, including metals, fabrics, woods and plastics. Conidia and hyphae became thick‐walled and melanized with time. There were significant ( P  <   0.001) differences in conidia/resting hyphae survival between carrier materials and between temperature regimes. At 23 °C/8 °C day/night, conidia and resting hyphae remained viable on steel, corrugated iron, galvanized steel, all tested fabrics, wood and random mixed materials for up to 8 months. At 36 °C/14 °C day/night, conidia and resting hyphae remained viable for up to 8 months, but only on cotton, denim, fleece, silk, leather, paper, plastic and all wood materials. At 45 °C/15 °C day/night, conidia and resting hyphae remained viable up to 8 months only on fleece wool, Eucalyptus marginata (jarrah wood) and paper. There were significant differences between carrier materials in their abilities to retain conidia and resting hyphae after washing ( P  <   0.001). Metabolic activity was confirmed for conidia and resting hyphae recovered after 8 months and K. caulivora colonies successfully re‐established on potato dextrose agar. Findings confirmed the critical importance of materials as long‐term carriers of viable K. caulivora conidia and resting hyphae, highlighting the potential for spread of a highly virulent K. caulivora race within and outside Australia via farming equipment, clothing and other associated materials. Results also have wider biosecurity implications for the transportation of fungal‐infested carrier materials previously considered as low risk.